Saving behavior and housing wealth: Evidence from German micro data - Sören Gröbel; Dorothee Ihle (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2016)
Housing property is the most important position in a household's wealth portfolio. Even though there is strong evidence that house price cycles and saving patterns behave synchronously, the underlying causes remain controversial. The present paper examines if there is a wealth effect of house prices on savings using household-level longitudinal data from the German Socio-Economic Panel for the period 1996-2012. We find that young renters increase and young homeowners decrease their savings in response to unanticipated house price shocks, whereas old households only hardly respond to house price changes. We interpret this as evidence of a housing wealth effect.
Keywords: D91; E21; R31; 330; housing wealth; saving behavior; SOEP; Germany